Surface engineering and the application of laser-based processes to stents - A review of the latest development - J. Dong (KeAi Communications Co., Ltd., 2022)
Late in-stent thrombus and restenosis still represent two major challenges in stents’ design. Surface treatment of stent is attracting attention due to the increasing importance of stenting intervention for coronary artery diseases. Several surface engineering techniques have been utilised to improve the biological response in vivo on a wide range of biomedical devices. As a tailorable, precise, and ultra-fast process, laser surface engineering offers the potential to treat stent materials and fabricate various 3D textures, including grooves, pillars, nanowires, porous and freeform structures, while also modifying surface chemistry through nitridation, oxidation and coatings. Laser-based processes can reduce the biodegradable materials' degradation rate, offering many advantages to improve stents’ performance, such as increased endothelialisation rate, prohibition of SMC proliferation, reduced platelet adhesion and controlled corrosion and degradation. Nowadays, adequate research has been conducted on laser surface texturing and surface chemistry modification. Laser texturing on commercial stents has been also investigated and a promotion of performance of laser-textured stents has been proved.In this critical review, the influence of surface texture and surface chemistry on stents performance is firstly reviewed to understand the surface characteristics of stents required to facilitate cellular response. This is followed by the explicit illustration of laser surface engineering of stents and/or related materials. Laser induced periodic surface structure (LIPSS) on stent materials is then explored, and finally the application of laser surface modification techniques on latest generation of stent devices is highlighted to provide future trends and research direction on laser surface engineering of stents.